2013
DOI: 10.1590/s1517-83822013005000055
|View full text |Cite
|
Sign up to set email alerts
|

Genetic profiling of Klebsiella pneumoniae: comparison of pulsed field gel electrophoresis and random amplified polymorphic DNA

Abstract: In this study, the discriminatory power of pulsed field gel electrophoresis (PFGE) and random amplified polymorphic DNA (RAPD) methods for subtyping of 54 clinical isolates of Klebsiella pneumoniae were compared. All isolates were typeable by RAPD, while 3.6% of them were not typeable by PFGE. The repeatability of both typing methods were 100% with satisfying reproducibility (≥ 95%). Although the discriminatory power of PFGE was greater than RAPD, both methods showed sufficient discriminatory power (DI > 0.95)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In the same way, several studies between 2008 and 2012 on K. pneumoniae isolates in Iran indicated the genotype diversity among isolates of this bacterium. [ 23 28 34 35 36 37 ] However, there are studies that have reported less diversity and more genotype similarity among isolates. [ 38 39 40 41 ] One explanation could be the fact that the most isolates in the above study were from limited sources in one hospital.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, several studies between 2008 and 2012 on K. pneumoniae isolates in Iran indicated the genotype diversity among isolates of this bacterium. [ 23 28 34 35 36 37 ] However, there are studies that have reported less diversity and more genotype similarity among isolates. [ 38 39 40 41 ] One explanation could be the fact that the most isolates in the above study were from limited sources in one hospital.…”
Section: Discussionmentioning
confidence: 99%
“…For RAPD typing, isolates that possessed two or more β-lactamase genes were chosen with the majority of isolates being those recovered in 2015. RAPD-PCR was chosen because it is a rapid and simple method which when optimized has proven competitive with the gold standard of pulse field gel electrophoresis [ 26 , 27 ]. RAPD1, also referred to as Primer 640 by other authors [ 13 , 26 ], proved to be optimal for DNA fingerprinting since it allowed the clear distinction of DNA banding patterns for all of the isolates tested.…”
Section: Discussionmentioning
confidence: 99%
“…The digested DNA was then separated in a 1% SeaKem Gold agarose (LONZA, Rockland, ME, United States) with pulse time of 6–36 s for 18.5 h at 14°C and constant voltage of 6 V/cm. The patterns were analyzed and compared using BioNumerics software version 6.5 ( Ashayeri-Panah et al, 2013 ). Genotyping for KP1276 was determined using 7 housekeeping genes ( gapA , infB , mdh , pgi , phoE , rpoB , and tonB ), and the MLST method was described previously ( Diancourt et al, 2005 ).…”
Section: Methodsmentioning
confidence: 99%